Odpowiedzi

2009-09-13T20:24:59+02:00
-2-8-6+4=-12
12+16-6+20=42
-20+5-17+3= -29
3+10+12=25
11-14-16+13=6
-12+6+4-9=1
4-7+4-3=-2
-16+6-9=-19
2009-09-13T20:27:27+02:00
(-2)+(-8)-(+6)-(-4)=-20
(+12)-(-16)-(+6)+(+20)=2
-20-(-5)+(-17)-(-3)=-45
(-4+7)-(-10-12)=-25
-(-11+14)-(16-13)=-6
-(12-6)+(4-9)=-11
-(-4)+(-7)-(-4)-(+3)=-12
-7-9+(-6)-(-9)= -17
Najlepsza Odpowiedź!
2009-09-13T20:33:55+02:00
(-2)+(-8)-(+6)-(-4)= -2 -8 -6 + 4 = -12
(+12)-(-16)-(+6)+(+20)= 12+16-6+20 = 42
-20-(-5)+(-17)-(-3)= -20 + 5 - 17 + 3 = -29
(-4+7)-(-10-12)= 3-22 = -19
-(-11+14)-(16-13)= -3 -3 = -6
-(12-6)+(4-9)=-6 -5 = -11
-(-4)+(-7)-(-4)-(+3)= 4 - 7 + 4 - 3 = -2
-7-9+(-6)-(-9)= -7 - 9 -6 +9= -15